FRANZ WERFEL’S "THE FORTY DAYS OF MUSA DAGH", A PERPETUALLY PRESENT PRODUCTION RATHER THAN A PRODUCT - Peroomian, Rubina (Armenian Folia Anglistika, 2024)
The article is a tribute to the 90th anniversary of Franz Werfel’s renowned novel The Forty Days of Musa Dagh. Borrowing Roland Barthes’ approach to texts – regarding their function and effects – and his explanation of writerly texts (scriptible), I see The Forty Days of Musa Dagh as one such text that, according to Barthes, is not a product but a production perpetually present, continuing to force the reader to participate, ponder and find a meaning or meanings, an entrance, among the plurality of entrances, an opening into the text. Ninety years after the publication of Franz Werfel’s literary masterpiece, there are still discussions ongoing and new insights being added. In my presentation, I will open my own way into the metamorphic perception of this timeless artistic creation by Diasporan Armenians and the world and focus on its function as the embodiment of the Armenian spirit of resistance to injustice, as a tool against the Turkish denial of the Armenian Genocide – the Turkish hysteria against this novel and repression of European governments to denounce it is further proof of its power – its effect on the self-realization and reawakening of the generations of Armenians on the verge of assimilation. I have often spoken and written about the impact of genocide literature on the understanding of the scope of the calamity and the universal truth that lies at the roots of factual writings and documents. The Forty Days of Musa Dagh is the most expressive voice in the history of the Armenian Genocide, an unequivocal representation of the horrifying reality, the prototype of the crime against humanity, ultimately playing a major role in influencing and inspiring Rafael Lemkin to devise the word “genocide”. I will point to why and how about 312 passages totalling 1062 lines, that is 11% of the original was omitted in the first English translation and reinstated in the new, 2012 version. The ensuing enthusiastic salutation of this new publication is representative of Diasporan Armenians’ continuing devotion to the book and the author.